Everything Changes - Martin, Ann. (NY : Scholastic, 1999)
It's a summer the girls will never forget. Some are leaving the club, others are beginnig new friendships, old boyfriends troubles and tough decisions awaite them.
720
Keywords: Teenage girls -- Fiction; Boyfriend -- Fiction; Summer -- Fiction; Clubs -- Fiction; Baby-sitters -- Fiction